EFL Learners’ Motivation in English Camp Setting: Self-Determination Theory Perspective - Bian Candra Garhani; Yusup Supriyono (Siliwangi University, 2021)
A numerous study focused on learners’ motivation using Self-determination Theory perspective in language learning has documented in ESL/EFL Context. However, there is still limited study that investigates motivation in self-determination theory where the context in language learning particularly in English camp. Hence, this study investigates the perceived motivation using Self-determination theory by EFL learners in English Camp Program. Case study used as a research design which is to investigate the phenomenon of motivation in English camp. The data were collected from four learners as the participants in English Camp Program by semi-structured interviews and analyzed qualitatively using thematic analysis. In sum up, this study discovered that English Camp able to create autonomous motivation through authentic learning, effective teaching strategy, and tutors as an agents’ roles. In the end, the contribution of this study is to facilitate educator, especially in English language learning to create high-quality motivation.